Differences in the quality of paranasal sinuses CT images in sinusitis case by slice thickness variations - Muhamad Faik; Rini Indrati (International Journal of Health Science and Technology, 2022)
One of the parameters that has an effect on the quality of paranasal sinuses CT image is slice thickness. According to Zojaji et al (2015), paranasal sinuses CT Scan with an indication of sinusitis should be made with a slice thickness of 5 mm, while at the Department of Radiology of Telogorejo Hospital Semarang, paranasal sinuses CT Scan is made with a slice thickness of 3.2 mm. This study aims to find out the effect of variations in slice thickness setting in imaging quality and determine the best setting of the three selected slice thicknesses in producing high quality of the paranasal sinuses CT image. This study was conducted at the Department of Radiology of Telogorejo Hospital, Semarang. The research sample is a paranasal sinuses CT of coronal slices in cases of sinusitis taken by accidental sampling techniques. Data regarding the quality of the paranasal sinuse CT image were collected through a check list by five radiologists. The results of the study showed that there were differences in the quality of images by three slice thicknesses. The three best slice thickness settings to produce high quality image were 3.2 mm, then 5 mm and the last 7.5 mm.